Aging and emotional expressions: is there a positivity bias during dynamic emotion recognition? - Di Domenico, Alberto; Palumbo, Rocco; Mammarella, Nicola; Fairfield, Beth (Frontiers in Psychology, 2015)
In this study, we investigated whether age-related differences in emotion regulation priorities influence online dynamic emotional facial discrimination. A group of 40 younger and a group of 40 older adults were invited to recognize a positive or negative expression as soon as the expression slowly emerged and subsequently rate it in terms of intensity. Our findings show that older adults recognized happy expressions faster than angry ones, while the direction of emotional expression does not seem to affect younger adults’ performance. Furthermore, older adults rated both negative and positive emotional faces as more intense compared to younger controls. This study detects age-related differences with a dynamic online paradigm and suggests that different regulation strategies may shape emotional face recognition.